Factors Related to Patient Satisfaction Level of Thyroid Tumor on PostOperative Thyroidectomy Scar Based on Patient Scar Assessment Scale (PSAS) in General Hospital Dr. M. Djamil Padang - Defri Heryadi; Daan Khambri; Rony Rustam (Biomedical Journal of Indonesia, 2021)
Introduction : Dr. M. Djamil Padang General Hospital (RSUP) still applies conventional methods as thyroidectomy treatment. Satisfaction and comfort to the scar is one of the issues because conventional thyroidectomy surgery scars are located in the neck area that will affect the confidence of patients, especially women. Method: This research was a quantitative research using cross sectional study design. The research was conducted at The Oncology Surgery Polyclinic of RSUP Dr.M. Djamil Padang with a sample of 50 respondents. Result: More than half of thyroid tumor patients found were women (56%), most patients had total thyroidectomy surgery (70%) with malignan tumor type (72%), and the most tumor size in the T4 group (52%). The average age of patients during surgery was 54.26 years. The average patient satisfaction score for post-thyroidectomy scars was 14.72 with a total score of 16, the lowest score was 6 and the highest score was 22. Significant relationships were found in variable tumor size (p= 0.000), type of surgery (p= 0.005), tumor type (p=0.004) and gender (p = 0.028), while there was no statistically significant relationship between age and patient satisfaction with postthyroidectomy scars (p=0,176). Conclusion: There were significant relationships between gender, type of surgery, type of tumor, tumor size to patient satisfaction with post-thyroidectomy scars, while age has no signifacnt relationship to patient satisfaction with post-thyroidectomy scars. A small number of PSAS score showed that the average patient was satisfied with post-thyroidectomy scar.